Staff Attitudes to Talking Openly About Ethical Dilemmas: The Role of Business Ethics Conceptions and Trust - Leila Trapp, N. (2011)
To ensure ethical employee behavior, companies often utilize several forms of mostly one-way communication such as codes of conduct. The extent to which these efforts, in addition to informing about the company stance on ethics, are able to positively influence behavior is disputed. In contrast, research on business ethics communication and behavior indicates a relatively clear, positive link between open workplace dialogue about ethical issues and ethical conduct. In this article, I therefore address the question: What influences employee attitudes to talking openly about ethical issues? Answers are proposed on the basis of focus group interviews with staff at the Denmark and Brazil affiliates of the global healthcare company Novo Nordisk. It was found that interest in discussing ethical issues was influenced by two main factors: employee conceptualizations of business ethics and the level of inter-collegial trust, credibility, and confidence. In this article, by examining these phenomena, I aim at providing insight that can both inform scholars in these fields as well as help managers in their attempts to promote open workplace dialogue about ethical issues.
Keywords: Trust; Organizational Behavior; Moral awareness; Ethics program; ethical decision-making; Dialogue; Communication